If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 2(z + 3) = -4(2z + 6) Reorder the terms: 6 + 2(3 + z) = -4(2z + 6) 6 + (3 * 2 + z * 2) = -4(2z + 6) 6 + (6 + 2z) = -4(2z + 6) Combine like terms: 6 + 6 = 12 12 + 2z = -4(2z + 6) Reorder the terms: 12 + 2z = -4(6 + 2z) 12 + 2z = (6 * -4 + 2z * -4) 12 + 2z = (-24 + -8z) Solving 12 + 2z = -24 + -8z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '8z' to each side of the equation. 12 + 2z + 8z = -24 + -8z + 8z Combine like terms: 2z + 8z = 10z 12 + 10z = -24 + -8z + 8z Combine like terms: -8z + 8z = 0 12 + 10z = -24 + 0 12 + 10z = -24 Add '-12' to each side of the equation. 12 + -12 + 10z = -24 + -12 Combine like terms: 12 + -12 = 0 0 + 10z = -24 + -12 10z = -24 + -12 Combine like terms: -24 + -12 = -36 10z = -36 Divide each side by '10'. z = -3.6 Simplifying z = -3.6
| 2y-3+3(3y+4)=-3(y+1) | | 1=3-c | | 2m+6=-10 | | 10/10-10/1 | | 10t+t+t-t-t=10 | | (4(y-6))/3=-2y | | -4(-m-5)-7=-11 | | 0=4p-28 | | x+10=x+90 | | 1/2x+5=1/2x-3 | | 5(p-6)=8p-21 | | -(9m+10)+2= | | 8u-8u+u-1=5 | | 12+2n=5n | | 7-5(x+8)=43 | | 8c+2b= | | 4(k+6)=56 | | -5x=3x+6 | | 9p-5p-9-2p=10 | | 6a-16=2(a-6) | | 16=6ty | | 16=6tyv | | 3.045+3b=2.73b+2.4+0.7b | | 8n+22=3 | | -7/2=-6/5x-7/3 | | 5+6p=41 | | -12/k=-4 | | 1(2x-4)=2(4-6x) | | 13/20-1/6 | | 18+6m=5+(-4m) | | 3(x-3)=6x-6-3x | | 70-42y-y=0 |